THE ROLE OF PHYSICAL CULTURE AND SPORTS IN COMBATING HARMFUL HABITS AND DEVIANT BEHAVIOR AMONG UNIVERSITY STUDENTS - Kasimova Iroda Khusan kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Deviant behavior is behavior that deviates from the generally accepted norms and rules in a given society. It can manifest in various forms, both negative (for example, crime, alcoholism, drug addiction) and positive (for example, social creativity).